REDUCING THE “JUSTICE GAP” THROUGH ACCESS TO LEGAL INFORMATION: ESTABLISHING ACCESS TO JUSTICE ENTRY POINTS AT PUBLIC LIBRARIES - Bilson, Beth; Lowenberger, Brea; Sharp, Graham (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
Among the strategies to improve public access to justice, increasing the accessibility and comprehensibility of legal information must be ranked as important. In this paper, the authors explore how libraries and librarians might play a role in providing the public with access and guidance to legal information. These issues are considered primarily in the context of two scenarios: that of the self-represented litigant, and that of a party to a limited scope retainer. The authors consider in particular how public libraries as a public space and public librarians as trusted intermediaries might support the objective of greater access. The possible roles of law society/courthouse and academic libraries in training and collection development are also considered. The distinction between providing access to legal information and giving legal advice is discussed briefly, and the authors suggest some possible ways of clarifying this distinction while pursuing the goal of expanding public access to legal information.